Expression and immunoassay application of full-length recombinant antibody recognizing chlorantraniliprole using Pichia pastoris expression system - Lianrun Huang; Panpan Cui; Yang Zhang; Yanling Wu; Yuan Ding; Maojun Jin; Xiude Hua (Crop Health, 2026)
Abstract Full-length recombinant antibodies (rAbs) expressed in yeast offer the advantage of a eukaryotic system ensuring proper folding and bioactivity, along with high yield and low cost. In this study, plasmids encoding the light chain and heavy chain of the anti-chlorantraniliprole monoclonal antibody (mAb) were constructed under the control of inducible alcohol oxidase promoters and equipped with secretory signal peptides. Subsequently, the rAb was expressed in Pichia pastoris and further utilized to develop a lateral flow immunoassay (LFIA). The visual limit of detection (vLOD) of the rAb-based LFIA was 0.63 ng/mL, which was twofold lower than that of the mAb-based LFIA. Validated via recovery experiments, the rAb-LFIA demonstrated that the vLOD of chlorantraniliprole in rice, apple, and grape samples complied with the maximum residue limits specified in Chinese and European Union food safety standards. Moreover, the rAb-LFIA exhibited reliability comparable to that of UPLC-MS/MS in the detection of blind samples.